A new species and new records of Cephennomicrus Reitter in Japan (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Twelve species of Cephennomicrus Reitter are currently known to occur in Japan, and four of them inhabit Okinawa Island. One more Okinawan species, Cephennomicrus tenebrosus sp. nov. is described. A new record of C. japonigenus (Jałoszyński & Hoshina) on Kyushu is given, and new collecting sites of the endemic Okinawan C. nagoanus Jałoszyński are reported. The distribution of Japanese Cephennomicrus species is summarized.